Kajian Ekologi Cerpen Digital Berbasis Web dan Implementasinya dalam Pembelajaran Bahasa dan Sastra - Rizam, Masyithah Maghfirah; Ayuanita, Kristanti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examines the ecological values in web-based digital short stories and their implementation in Indonesian Language and Literature learning. The data were collected from three short stories titled Penyumbang Sampah ke Sungai (Garbage Contributor to the River), Rumahku Kebanjiran (My House Flooded), and Banjir (Flood). This research employs a descriptive qualitative method with an ecocriticism approach to identify the ecological values embedded in these short stories. The findings reveal that the stories effectively depict the impact of human behavior on the environment, such as pollution, deforestation, and flooding. The ecological values in these stories can be implemented in learning to raise students' awareness of environmental issues, enhance critical thinking skills, and encourage real action in preserving nature. This study concludes that ecology-based digital literature can serve as a relevant and effective medium in language and literature learning, supporting environmental education in schools.